Produção de biogás a partir de bagaço de cana-de-açúcar após pré-tratamento com ácido cítrico diluído - Gomes, Michelle Garcia (2019)
Lignocellulosic residues, such as sugarcane bagasse, can be used as biomass for energy generation, in the conversion of liquid or gaseous biofuels, provided that a pretreatment is applied to the material by acidic, basic or even the use of specific enzymes for sugar solubilization and/or lignin removal. In this work, divided into 2 parts, we evaluated the best data treatment for better anaerobic biodegradability and potential in biogas production, from the pretreatment of sugarcane bagasse with dilute citric acid. To date, no studies have been conducted using this acid for this purpose and it has several advantages of use such as low toxicity, corrosivity and cost. In the first stage, the pre-treatment in reflux system (atmospheric pressure) was evaluated, using the experimental design (22), having as operational variables time (min) and citric acid concentration (%). In a second stage, pretreatment was performed in a pressurized system, optimized through the quadratic Doehlert (Pedersen and Meyer) experimental design, an experimental design (23). The variables evaluated were temperature (T, °C), time (t, min) and liquid solid ratio (RSL, g.mL-1). The efficiency of the pretreatments was evaluated by morphological and chemical characterization of the obtained solid fractions and quantification of fermentable sugars and inhibitors of the liquid fractions. Enzymatic hydrolysis was performed using Cellic® CTec 3 enzymatic complex and quantification of total reducing sugars (ART), as well as quantification of fermentable sugars (xylose, glucose and/or arabinose). In this context, the pre-treatment physicochemical design experimental 1 showed that the variables under study had no direct relationship with the content of lignin, cellulose and hemicelluloses. However, the structure was altered, improving pulp accessibility, which was confirmed in the higher concentrations of total reducing sugars compared to raw sugarcane bagasse. Sample 6 (6.0% and 102.43 min) had the lowest lignin content (22.6%), low crystallinity index (54%), fiber breakdowns (after pretreatment and after enzymatic hydrolysis ), high total reducing sugar concentration (28.21%), accumulated biogas volume of 55.14 NmL. Caloric power reached a value of 3019 Kcal/kg. In design experimental 2, pretreatment was more effective at design experimental 1, indicating structural changes in almost all samples in relation to raw sugarcane bagasse. The results suggest that RSL conditions of 9.75 g.mL-1, temperature at 120 °C and reaction time of 55 min (sample 2) caused lignin content in the range of 22%, cellulose content over 50 % and low hemicellulose content. Both solid fraction (after enzymatic hydrolysis) and liquid fraction (after pretreatment) showed high sugar release and consequently significant accumulated biogas volume values (449.41 and 209.45 NmL, respectively). The calorific value resulted in the value of 3294 Kcal/kg. Therefore, the results demonstrated the viability of the action of dilute citric acid under new experimental conditions for sugarcane bagasse pretreatment for promising biogas production.